Relation of early tumor shrinkage (ETS) observed in first‐line treatment to efficacy parameters of subsequent treatment in FIRE‐3 (AIOKRK0306) - Modest, Dominik P.; Stintzing, Sebastian; Fischer von Weikersthal, Ludwig; Decker, Thomas; Kiani, Alexander; Vehling‐Kaiser, Ursula; Al‐Batran, Salah‐Eddin; Heintges, Tobias; Lerchenmüller, Christian; Kahl, Christoph; Seipelt, Gernot; Kullmann, Frank; et al. (International journal of cancer, 2017)
We explored the association of early tumor shrinkage (ETS) and non‐ETS with efficacy of first‐line and consecutive second‐line treatment in patients with KRAS wild‐type metastatic colorectal cancer treated in FIRE‐3. Assessment of tumor shrinkage was based on the sum of longest diameters of target lesions, evaluated after 6 weeks of treatment. Shrinkage was classified as ETS (shrinkage by ≥ 20%), mETS (shrinkage by 0 to <20%), mPD (minor progression >0 to <20%) and PD (progression ≥20%). Overall survival (OS) was 33.2 (95% CI 28.0–38.4) months in ETS patients, while non‐ETS was associated with less favorable outcome (mETS 24.0 (95% CI 21.2–26.9) months, mPD 19.0 (95% CI 13.0–25.0) months, PD 12.8 (95% CI 11.1–14.5) months). Differences in PFS of first‐line therapy were less pronounced. ETS subgroups defined in first‐line therapy also correlated with efficacy of second‐line therapy. Progression‐free survival in second‐line (PFS2nd) was 6.5 months (5.8–7.2) for ETS, and was 5.6 (95% CI 4.7–6.5) months for mETS, 4.9 (95% CI 3.7–6.1) months for mPD and 3.3 (95% CI 2.3–4.3) months for PD. PFS of first‐line and PFS2nd showed a linear correlation (Bravais–Pearson coefficient: 0.16, p = 0.006). While ETS is associated with the most favorable outcome, non‐ETS represents a heterogeneous subgroup with distinct characteristics of less favorable initial tumor response to treatment. This is the first analysis to demonstrate that early tumor response observed during first‐line FOLFIRI‐based therapy may also relate to efficacy of second‐line treatment. Early response parameters may serve as stratification factors in trials recruiting pretreated patients. What's new? Early tumor shrinkage (ETS) is linked to favorable survival in metastatic colorectal cancer (mCRC). However, ETS occurs in only some patients, for reasons that remain unknown while non‐ETS patients represent a heterogeneous subgroup. Here, ETS and non‐ETS subgroups were examined in KRAS wild‐type mCRC patients enrolled in FIRE‐3, a trial comparing first‐line FOLFIRI (5‐fluorouracil, leucovorin, and irinotecan) plus cetuximab with FOLFIRI plus bevacizumab. Efficacy of first‐line FOLFIRI‐based therapy differed in ETS and non‐ETS subgroups, with the latter generally experiencing less‐favorable initial tumor responses. Patients who benefited from first‐line therapy tended to also benefit from second‐line therapy, supporting a role for efficacy parameters in mCRC patient stratification.